2020
DOI: 10.1101/2020.07.02.20144956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing Virus Test Capacity via Recursive Pool Testing with an Application to SARS-CoV-2 Testing

Abstract: In the context of adequate reactions to the current Covid-19 pandemic, Seifried, Ciesek et al. [6, 5] have proposed the application of SARS-CoV-2 pool testing in the pursuit of increasing testing capacity. We show how this method can be substantially improved in realistic scenarios, and we point out a possible impact on the ongoing discussion concerning the need of increased testing as a complementary measure to relaxed restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…While there is a relatively large amount of literature on optimal group testing strategies, there is little in the literature on the frequency for repeating pooled testing for SARS-CoV-2. 6 , 32 , 49 , 77 , 78 However, there is wide support for the concept of repeat pooled testing and its use in routine monitoring of populations such as workers. 5 , 21 , 22 , 31 , 48 , 54 , 56 Cabrera et al 22 concluded that after an institution achieved a prevalence of zero, and after exclusion of positive and symptomatic people, new cases identified by multiple rounds of screening using pooled testing would be presymptomatic or newly symptomatic individuals with viral loads just reaching their peak.…”
Section: Frequency Of Testingmentioning
confidence: 99%
“…While there is a relatively large amount of literature on optimal group testing strategies, there is little in the literature on the frequency for repeating pooled testing for SARS-CoV-2. 6 , 32 , 49 , 77 , 78 However, there is wide support for the concept of repeat pooled testing and its use in routine monitoring of populations such as workers. 5 , 21 , 22 , 31 , 48 , 54 , 56 Cabrera et al 22 concluded that after an institution achieved a prevalence of zero, and after exclusion of positive and symptomatic people, new cases identified by multiple rounds of screening using pooled testing would be presymptomatic or newly symptomatic individuals with viral loads just reaching their peak.…”
Section: Frequency Of Testingmentioning
confidence: 99%
“…In its simplest form, the pooling test works by constituting a set of individual samples, in the case where the pool is COVID-19 negative, all the individuals are identified as negative and if the pool is positive, further tests would be necessary to identify infected individuals in the group ( Dorfman, 1943 ; Olivier Gossner, 2020 ). This approach has been successfully used in the countries with high technological potential to deal with the lack of screening means ( Mutzel et al, 2020 ; Shani-Narkiss et al, 2020 ), as it has been proposed as a massive screening strategy ( De Salazar et al, 2020 ; Bilder and Tebbs, 2012 ).…”
Section: Introductionmentioning
confidence: 99%